2022
DOI: 10.2147/jir.s366903
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nomogram Integrated with Systemic Inflammation Markers and Traditional Prognostic Factors for Adverse Events’ Prediction in Patients with Chronic Heart Failure in the Southwest of China

Abstract: Inflammation contributes to the pathogenesis and progression of heart failure (HF). This study aimed to construct a nomogram based on systemic inflammatory markers and traditional prognostic factors to assess the risk of adverse outcomes (cardiovascular readmission and all-cause death) in patients with chronic heart failure (CHF). Methods: Data were retrospectively collected from patients with HF admitted to the Department of Cardiovascular Medicine at the First Affiliated Hospital of Chongqing Medical Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A study found that NLR can be used to predict the development of atrial fibrillation in diabetes patients [ 19 ]. A high NLR in conjunction with neutrophil transcriptional activation is associated with systemic inflammation and functional impairment in HF with preserved ejection fraction (HFpEF) [ 4 ].—Liu Z established a novel nomogram integrated with LMR (HR: 0.85, 95% CI: 0.78–0.93) and PLR (HR: 1.002, 95% CI: 1.000–1.004) to evaluate the risk of cardiovascular readmission or all-cause mortality in patients with CHF [ 20 ]. The above are consistent with our research results and verified synchronously in the same large sample population based on NHANES data.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that NLR can be used to predict the development of atrial fibrillation in diabetes patients [ 19 ]. A high NLR in conjunction with neutrophil transcriptional activation is associated with systemic inflammation and functional impairment in HF with preserved ejection fraction (HFpEF) [ 4 ].—Liu Z established a novel nomogram integrated with LMR (HR: 0.85, 95% CI: 0.78–0.93) and PLR (HR: 1.002, 95% CI: 1.000–1.004) to evaluate the risk of cardiovascular readmission or all-cause mortality in patients with CHF [ 20 ]. The above are consistent with our research results and verified synchronously in the same large sample population based on NHANES data.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia, particularly persistent and new-onset anemia and milder temporary anemia, are suggested to be harmful to HF patients [23]. Inflammatory markers have been confirmed to be associated with adverse outcomes in HF patients [24]. NT-ProBNP secreted by the ventricle with increased wall stress is a prognostic HF biomarker [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is often used in the medical field for the prediction of adverse events of diseases, such as the prediction of adverse events of chronic heart failure. 14 At present, the nomogram prediction model has also been studied for the prediction of clinical metastasis of NSCLC, 15 and the novel International Association for the Study of Lung Cancer (IASLC) grade of invasive lung adenocarcinoma, 16 all of which reflect a good adjuvant effect in the treatment of patients.…”
Section: Introductionmentioning
confidence: 99%